2021
DOI: 10.1371/journal.pone.0258345
|View full text |Cite
|
Sign up to set email alerts
|

Soccer-related injuries utilization of U.S. emergency departments for concussions, intracranial injuries, and other-injuries in a national representative probability sample: Nationwide Emergency Department Sample, 2010 to 2013

Abstract: Soccer participation in the United States (U.S.) has increased over time, and injuries as well as interest to prevent injuries has become more common. This study described Emergency Department (ED) visits related to concussions, intracranial injuries (ICI), and all-other injuries attributed to soccer play; described healthcare cost and length of hospital stay of soccer-related injuries; and determined independent predictors of concussions, ICI, and all-other soccer injuries leading to ED visits. The study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In our study, different from the literature, we also detected a high frequency of thorax injuries. In the literature examining football injuries, thorax injuries are generally included in multiple or trunk injuries [12,13]. Padegimas et al reported that the rate of emergency department presentations was high in the presence of sports-related thorax injuries [14].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, different from the literature, we also detected a high frequency of thorax injuries. In the literature examining football injuries, thorax injuries are generally included in multiple or trunk injuries [12,13]. Padegimas et al reported that the rate of emergency department presentations was high in the presence of sports-related thorax injuries [14].…”
Section: Discussionmentioning
confidence: 99%